2001
DOI: 10.1016/s0377-0427(00)00255-7
|View full text |Cite
|
Sign up to set email alerts
|

How We solve PDEs

Abstract: Time to solution I n t e n s i t y R a t e O p e r a t i o n s p e r b y t e t r a n s f e r r e d D Abstract. Important computational physics problems are often large-scale in nature, and it is highly desirable to have robust and high performing computational frameworks that can quickly address these problems. However, it is no trivial task to determine whether a computational framework is performing efficiently or is scalable. The aim of this paper is to present various strategies for better understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Consider the Lagrange form of s(x) (15). Note that we can expand φ( x − x i ) and L 2 φ( x − x i ) in powers of ε 2 so that the coefficients in front of these powers will be some polynomial in x.…”
Section: Some Theoretical Results On the ε → 0 Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the Lagrange form of s(x) (15). Note that we can expand φ( x − x i ) and L 2 φ( x − x i ) in powers of ε 2 so that the coefficients in front of these powers will be some polynomial in x.…”
Section: Some Theoretical Results On the ε → 0 Limitmentioning
confidence: 99%
“…However, this approach also raises the question of how the weights of the scattered node FD formulas should be computed. Abgrall [14] and Schönauer and Adolph [15], for example, propose extending the classical polynomial interpolation technique. This idea, however, has not become widely used, partly because it leads to several ambiguities about how to generate the FD formulas.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the best known approach to the generation of finite difference stencils on irregular centres is the polynomial least squares method [19,23,38,3]. This and related methods are often understood as local collocation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this, generalised finite difference methods allow a lot of flexibility in the choice of stencil supports. For the polynomial methods, sophisticated algorithms have been developed, see [38,20,35]. We are not aware, however, of any work in this direction for the RBF based generalised finite differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, no further discussion is provided of the general conditions under which singularities occur. The singularity problem for moving least squares has also been noted by Netuzhylov [4] and Prax et al [5], and for a similar problem by Schoenauer and Adolph [6], who also observed the occurrence of singularities when the data points lie along straight lines. However, to the best knowledge of the authors, a general theory for predicting the occurrence of singularities in moving least squares has never been published.…”
Section: Introductionmentioning
confidence: 56%